El estudio de la arquitectura empresarial en el ámbito de los negocios: Una aproximación bibliométrica; Study of business architecture in business context: A bibliometric approach - Suly Sendy Pérez Casta\~neda; Elkin Darío Rave Gómez; César Alveiro Montoya Agudelo (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– As technology ceases to be a privilege in organizations to become a basic requirement in any business sector, especially after the Covid 19 pandemic, enterprise architecture becomes a technology management tool to improve the performance of companies, hence the importance of studying their evolution, current status and trends through a bibliometric analysis that allows building a foundation for future research. The methodology used identifies the scientific production regarding its quantity, quality, structure and trends through the use of automated algorithms in the bibliometrix and biblioshiny applications, in 1,091 scientific papers published from 2011 to 2022.The results show a slightly upward linear scientific production, with references in authors and impact located mainly in developed countries, such as the United States, the United Kingdom, Germany and with the presence of emerging countries such as China and India. Regarding the structure of the theme, the clusters related to technology and information are the predominant ones, although themes such as innovation and business models begin to show connections with the study of enterprise architecture. Finally, regarding the study trend, until 2020 the topics were focused on technology and information, changing towards sustainable development, the internet of things, business models, digital transformation, blockchain and case of studies, which shows the insertion of this study in the business field.
Keywords: M15; O32; Y3; 330; Technology; enterprise architecture; bibliometric analysis; business